KAIDAH FIKIH TENTANG SYARAT DAN APLIKASINYA DALAM HUKUM MU’AMALAH MALIYYAH - Agus Putra, Panji Adam (Universitas Muhammadiyah Ponorogo, 2023)
Fiqh rules have a role in the legal istinbath process, especially in contemporary legal issues such as sharia economics or muamalah transactions. One of the problems in muamalah is related to the terms of an agreement (contract). This study aims to determine the principles of fiqh relating to terms and their application in sharia economic transactions. This study uses a qualitative method with a normative juridical approach. This research includes the type of literature study research. The primary data sources used were books on fiqh principles (al-qawâ'id al-fiqhiyyah), secondary sources in this study were articles in journals, as well as books/books on relevant fiqh rules. The results show that the fiqh rules relating to conditions include must meet the requirements as much as possible, something that depends on certain conditions, then the legal provisions must exist if the conditions exist, promises in the form of ta'lîq (hanging) are binding (must be fulfilled), anyone who imposes something on himself voluntarily without coercion, then that something becomes his obligation, any conditions that differ from sharia principles are vanity.